Impacts of forest conservation on local agricultural labor supply: Evidence from the Indonesian forest moratorium. Issue 3 (7th September 2022) - Xu, Shang; Klaiber, H. Allen; Miteva, Daniela A.
Abstract: Tropical forest conservation is critical for reducing greenhouse gas emissions and maintaining global ecosystems. Understanding the channels through which conservation affects agricultural activities and livelihoods in these regions is key to designing effective policies and promoting sustainable development. To this end, we use labor supply data from Indonesia in 2007 and 2015 combined with a matching strategy to estimate the impacts of a national forest conservation policy, the forest moratorium, on local agricultural labor. Consistent with the predictions of our theoretical model, we find robust empirical evidence that the moratorium increased local agricultural employment and slowed structural transformation away from the agricultural sector. We provide corresponding evidence of decreased household expenditure due to the moratorium. Despite the moratorium, we find significant deforestation and forest degradation within the boundaries of the moratorium‐targeted areas, suggesting that increases in local agricultural employment may partly dampen the conservation policy's effectiveness. Our work offers new insights into evaluating existing conservation policies and designing future policies for Indonesia and other resource‐dependent economies that face similar challenges in balancing economic growth with conservation.